2003
DOI: 10.3758/bf03194803
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory temporal order judgments: When two locations are better than one

Abstract: In Experiment 1, participants were presented with pairs of stimuli (one visual and the other tactile) from the left and/or right of fixation at varying stimulus onset asynchronies and were required to make unspeeded temporal order judgments (TOJs) regarding which modality was presented first. When the participants adopted an uncrossed-hands posture, just noticeable differences (JNDs) were lower (i.e., multisensory TOJs were more precise) when stimuli were presented from different positions, rather than from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
94
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(108 citation statements)
references
References 66 publications
(84 reference statements)
12
94
0
Order By: Relevance
“…The possibility that crossed hands effects in the tactile modality only occur in the presence of incongruent visual distractors is an interesting one, and is worthy of further research (see also the discussion of this point in ref [24]). Perhaps it is only in the presence of additional visual stimulation in close temporal sequence that tactile crossed hands effects may arise for non-spatial discrimination tasks, suggesting that crossed hands impairments may be due to the conflict between external, allocentric, and internal, somatotopic coordinates.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that crossed hands effects in the tactile modality only occur in the presence of incongruent visual distractors is an interesting one, and is worthy of further research (see also the discussion of this point in ref [24]). Perhaps it is only in the presence of additional visual stimulation in close temporal sequence that tactile crossed hands effects may arise for non-spatial discrimination tasks, suggesting that crossed hands impairments may be due to the conflict between external, allocentric, and internal, somatotopic coordinates.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, using different auditory attributes other than pitch (amplitude modulation, left/right ear alternation) had little effects on the temporal binding limit (electronic supplementary material, figure S5). Sixth, the temporal binding limit of cross-attribute binding remained to be 2-3 Hz even when it was measured under more natural binding situations with regard to spatial alignment (Spence et al 2003) and attribute combination (e.g. Maeda et al 2004; electronic supplementary material, figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…First, visual and tactile stimuli appearing simultaneously and spatially close on a participant's body, can give rise to congruence effect, even when participants are aware of the potential conflict between them (see Rock & Victor 1964). Previous multisensory studies showed that integration between two sensory modalities is strongly temporally (Shore et al 2002;Spence et al 2003;Yamamoto & Kitazawa 2001) and spatially dependent (Spence et al 1998;Pavani et al 2000). In our study, visual-tactile integration is defined over very specific body parts that lie very close together in external space, their spatial disparity being no more than the few centimeters separating D3 and D4.…”
Section: Discussionmentioning
confidence: 99%